2021
DOI: 10.1590/0001-3765202120190909
|View full text |Cite
|
Sign up to set email alerts
|

Codimension one distributions and stable rank 2 reflexive sheaves on threefolds

Abstract: We show that codimension one distributions with at most isolated singularities on certain smooth projective threefolds with Picard rank one have stable tangent sheaves. The ideas in the proof of this fact are then applied to the characterization of certain irreducible components of the moduli space of stable rank 2 reflexive sheaves on P 3 , and to the construction of stable rank 2 reflexive sheaves with prescribed Chern classes on general threefolds. We also prove that if G is a subfoliation of a codimension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In [6] we have proved that codimension one distribution with at most isolated singularities on certain smooth projective threefolds with Picard rank one have also stable tangent sheaves. As a consequence we provide a characterization of certain irreducible components of the moduli space of stable rank 2 reflexive sheaves on P 3 , and we are able to give the construction of stable rank 2 reflexive sheaves with prescribed Chern classes on general threefolds.…”
Section: Moduli Of Distributions Singular Schemes and Classification ...mentioning
confidence: 99%
“…In [6] we have proved that codimension one distribution with at most isolated singularities on certain smooth projective threefolds with Picard rank one have also stable tangent sheaves. As a consequence we provide a characterization of certain irreducible components of the moduli space of stable rank 2 reflexive sheaves on P 3 , and we are able to give the construction of stable rank 2 reflexive sheaves with prescribed Chern classes on general threefolds.…”
Section: Moduli Of Distributions Singular Schemes and Classification ...mentioning
confidence: 99%
“…In [2,Theorem 1], the authors proved that, under the conditions above, T D is a stable rank 2 reflexive sheaf. Moreover, it was shown that there exists a non-singular, rational, irreducible component of the moduli space of stable rank 2 reflexive sheaves on P 3 whose general point corresponds to the tangent sheaf of a generic distribution.…”
Section: Introductionmentioning
confidence: 99%
“…In [26], it is shown that the codimension one distributions with at most isolated singularities on certain smooth projective 3-folds with Picard group rank 1 have µ-stable tangent sheaves. Moreover, the authors characterized certain irreducible components of the moduli space rank 2 reflexive sheaves on P 3 .…”
Section: The Moduli Space Of Stable Rank 2 Sheaves On Q 3 With Chern ...mentioning
confidence: 99%
“…In the next section we present the concept of distributions and foliations on smooth projective threefolds. We use [1,25,26] as our main references.…”
Section: Distributions and Foliations On 3-fold Hypersurfacesmentioning
confidence: 99%
See 1 more Smart Citation